Deans’ roles in governance practices in selected public universities, Pakistan - Shah, Shakeela (2016)
University governance is about allocation of power, roles and responsibilities in university administration practices. There are perplexing questions on who should have the power, who should lead and govern the universities especially public universities. Unclear allocation of power and ambiguity of roles of stakeholders in the governance process especially the deans have made their roles ineffective. The objective of this study was to examine the deans’ roles and power allocated to them in governance practices in selected public universities in Pakistan. This study also explored how deans’ roles are understood by various stakeholders as well as the extent of the deans’ involvement in the governance process in the selected public universities. This is a qualitative research and sixteen university stakeholders comprising deans, vice chancellors, pro vice chancellors, and directors of quality enhancement sections were interviewed using a semi-structured interview protocol to explore their understanding and interpretations about the governance process. The interviews lasted between 50 to 80 minutes and were recorded in a digital audio recorder. Data analysis was carried out in two phases. First, the interviews were transcribed and documents were analyzed accordingly. Second phase involved the thematic data analysis through open coding, axial coding and selective coding. The results revealed the existence of strong policies developed by the government. However, according to the deans, there are no clear defined legislation until now, laws are outdated and not amended in line with the university development. Governance system was perceived as working on adhocism, following traditional rules, procedures and practices. The Chancellor and vice chancellor are the only authorities and have excessive powers as understood by the deans. It was felt that the system was overcentralized, governance framework was inadequate to meet the challenges of modern time and was strongly influenced by the government political aspirations. In practice, there were differences in understanding and interpretations on the involvement of the deans in governance processes due to roles conflicts and roles ambiguity. The university top management perceived the deans as the academic leaders of the respective faculties, having the relevant power to decide for faculty affairs, but the deans regard themselves as powerless. The study recommends that the present laws on university governance to be re-looked, the constitutional framework on university governance has to be amended and improved, and the allocation of powers as well as the deans’ roles to be described clearly in the university constitution so that the future deans could functions effectively in the governance process.